2016
DOI: 10.14742/ajet.2528
|View full text |Cite
|
Sign up to set email alerts
|

e-Portfolios enhancing students’ self-directed learning: A systematic review of influencing factors

Abstract: e-Portfolios have become increasingly popular among educators as learning tools. Some research even shows that e-portfolios can be utilised to facilitate the development of skills for self-directed learning. Such skills include self-assessment of performance, formulation of learning goals, and selection of future tasks. However, it is not yet clear under which conditions e-portfolios optimally facilitate the development of these skills. We conducted a systematic review aimed at identifying and understanding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 29 publications
4
84
0
8
Order By: Relevance
“…A recent, systematic review performed at Maastricht University also shows perception of student autonomy to be one of the factors influenced by the use of e-portfolios (Beckers, Dolmans, & van Merriënboer, 2016). Studies show that e-portfolios can be used to facilitate the development of competencies for self-directed learning.…”
Section: Discussionmentioning
confidence: 99%
“…A recent, systematic review performed at Maastricht University also shows perception of student autonomy to be one of the factors influenced by the use of e-portfolios (Beckers, Dolmans, & van Merriënboer, 2016). Studies show that e-portfolios can be used to facilitate the development of competencies for self-directed learning.…”
Section: Discussionmentioning
confidence: 99%
“…Their review of Higher Education Institutions found top-down support is needed to establish clarity of purpose and course integration. An increased role in providing support for self-directed learning as reported by Beckers (Beckers, Dolmans and van Merrienboer, 2016) may go some way to achieving this goal.…”
Section: Discussionmentioning
confidence: 99%
“…In detail some studies have also demonstrated the benefits of open learning, have been mentioned in previous studies and have also described the concept of MOOCs and e-portfolios, the differences and similarities between them shown. The presentation of learning objects developed by the students themselves has drawn the benefits of using how to realize the construction of scholarship for students (Beckers et al, 2016;Brennan, 2013;Britten and Mullen, 2003;TOSUN and BARIŞ, 2011;Tubaishat, 2014). Thus, it aims to form the basis for the concept of learning object and explain that the learning object developed by the students themselves can be used in different format and flexible in education.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, individual development, learning and learning and the active participation of learners are essentially capable of enhancing contextual thinking (Horvat et al, 2015). Learning objects prioritizing assignments and student studies are one of the principles of the approach (Beckers et al, 2016).…”
Section: Figure 1 Student Activity Data View Learning Object From Abroadmentioning
confidence: 99%